2012
DOI: 10.3945/jn.112.162362
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Ferritin Concentration Is Positively Associated with Newborn Iron Stores in Women with Low Ferritin Status in Late Pregnancy

Abstract: Iron deficiency (ID) is common in pregnant women and infants, particularly in developing countries. The relation between maternal and neonatal iron status remains unclear. This study considered the issue in a large sample of mother-newborn pairs in rural southeastern China. Hemoglobin (Hb) and serum ferritin (SF) were measured in 3702 pregnant women at ≥37 wk gestation and in cord blood of their infants born at term (37-42 wk gestation). Maternal anemia (Hb <110 g/L) was present in 27.5% and associated with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
140
5
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(168 citation statements)
references
References 53 publications
(61 reference statements)
9
140
5
14
Order By: Relevance
“…A recent study in China, which included a large sample of mother-child pairs (n ¼ 3702), detected a strong correlation between maternal and neonatal ferritin in women whose plasma ferritin levels fell below a threshold of depletion, with every unit of decrease in maternal serum ferritin corresponding to a 2.4-unit drop in cord ferritin. 118 This finding is consistent with rodent data indicating a "broken stick" relationship between maternal and fetal iron parameters, suggesting a critical point below which the two become dependent. 102 While most mechanistic studies are modeled on healthy pregnancy, it is worth noting that conditions with underlying placental abnormalities, such as intrauterine growth restriction and gestational diabetes, may disrupt the normal regulatory mechanism of the placenta and negatively affect fetal iron transfer.…”
Section: Regulation Of Iron Transport Across the Placentasupporting
confidence: 82%
“…A recent study in China, which included a large sample of mother-child pairs (n ¼ 3702), detected a strong correlation between maternal and neonatal ferritin in women whose plasma ferritin levels fell below a threshold of depletion, with every unit of decrease in maternal serum ferritin corresponding to a 2.4-unit drop in cord ferritin. 118 This finding is consistent with rodent data indicating a "broken stick" relationship between maternal and fetal iron parameters, suggesting a critical point below which the two become dependent. 102 While most mechanistic studies are modeled on healthy pregnancy, it is worth noting that conditions with underlying placental abnormalities, such as intrauterine growth restriction and gestational diabetes, may disrupt the normal regulatory mechanism of the placenta and negatively affect fetal iron transfer.…”
Section: Regulation Of Iron Transport Across the Placentasupporting
confidence: 82%
“…According to Wang et al, the impact of iron supplementation in pregnancy on the birth weight of the child depends on the concentration of hemoglobin in maternal blood before pregnancy [9]. A significant decrease in fetal iron was observed in pregnant women with anemia [10].…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, the body's iron requirement significantly increases, especially in the third trimester [9,10]. Preg- nant women are therefore advised to use iron and folic acid supplements to reduce the risk of developing anemia [8].…”
Section: Ironmentioning
confidence: 99%
“…Numerous and compelling scientific evidence has shown that IDA during pregnancy is linked with a wide variety of adverse maternal and perinatal outcomes, such as preterm birth, low birth weight and unhealthy neurodevelopment in the fetus (16). And it is now clear that neonatal iron stores can be compromised when the mother is iron deficient or anemic (17).…”
Section: Discussionmentioning
confidence: 99%